2021
DOI: 10.1098/rsos.201127
|View full text |Cite
|
Sign up to set email alerts
|

The significance of long-range correction to the hydroperoxyl radical-scavenging reaction of trans-resveratrol and gnetin C

Abstract: Density functional theory has been gaining popularity for studying the radical scavenging activity of antioxidants. However, only a few studies investigate the importance of calculation methods on the radical-scavenging reactions. In this study, we examined the significance of (i) the long-range correction on the coulombic interaction and (ii) the London dispersion correction to the hydroperoxyl radical-scavenging reaction of trans-resveratrol and gnetin C. We employed B3LYP, CAM-B3LYP, M06-2X exchange-correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The IC 50 values of free R, RNP-1, RNP-2, and Vc against ABTS radicals were 0.006, 0.007, 0.008, and 0.030 mg/mL, respectively. It has been reported that R is a good hydrogen atom donor that exhibits strong antioxidant activity against various free radicals . Our result showed that both RNP-1 and RNP-2 have DPPH- and ABTS-scavenging capacities comparable with that of free R. The encapsulation process did not adversely affect R’s antioxidant activity.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…The IC 50 values of free R, RNP-1, RNP-2, and Vc against ABTS radicals were 0.006, 0.007, 0.008, and 0.030 mg/mL, respectively. It has been reported that R is a good hydrogen atom donor that exhibits strong antioxidant activity against various free radicals . Our result showed that both RNP-1 and RNP-2 have DPPH- and ABTS-scavenging capacities comparable with that of free R. The encapsulation process did not adversely affect R’s antioxidant activity.…”
Section: Resultsmentioning
confidence: 47%
“…It has been reported that R is a good hydrogen atom donor that exhibits strong antioxidant activity against various free radicals. 39 Our result showed that both RNP-1 and RNP-2 have DPPH-and ABTS-scavenging capacities comparable with that of free R. The encapsulation process did not adversely affect R's antioxidant activity. Both void NP-1 and void NP-2 showed no DPPH-and ABTSscavenging ability.…”
Section: Preparation and Characterization Of Nanoparticlesmentioning
confidence: 50%
“…Despite having excellent thermodynamic parameters, the Γ value of 10b-CH is below 1%, indicating this site has a negligible impact on antioxidative properties. Such contrasting thermodynamics and kinetics phenomenon of CH abstraction were also found in artepillin C [55], some lignans [56] and gnetin C [57].…”
Section: Feasibility Study Of • Ooh Scavenging Sites Via Thermodynami...mentioning
confidence: 86%
“…Therefore, geometry optimization of all structures in their closed-shell singlet ground states was performed at B3LYP-D3/6-311G(d,p) level of theory in a gas phase. D3 denotes the empirical Grimme dispersion corrections (D3) [ 59 ], which were included in the calculations due to their importance in the radical study [ 60 ]. Radicals represent an open-shell system, so an unrestricted formalism was used in the calculations.…”
Section: Methodsmentioning
confidence: 99%